(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
"Increased Immune Deficiency Syndrome" and "Acquired Immune Deficiency" are on the rise throughout the world today. It is very necessary that we get such diseases. What is AIDS and HIV disease? How does it affect patients? Will people who are infected with this disease recover? How can we prevent such a disease? In the early stages of AIDS, we can also use , NurZam’’ drugs, because in the disease of increased immune deficiency, immunity decreases, and this drug improves the immune system.